2021
DOI: 10.1007/s00049-021-00360-6
|View full text |Cite
|
Sign up to set email alerts
|

Soybean leaf age and plant stage influence expression of resistance to velvetbean caterpillar and fall armyworm

Abstract: Numerous species of herbivorous insects are associated with soybeans, including the specialist velvetbean caterpillar (VBC), Anticarsia gemmatalis, and the generalist fall armyworm (FAW), Spodoptera frugiperda. Expression of plant resistance is in uenced by factors intrinsic to host plants, such as leaf age and plant stage, which can differentially affect specialist and generalist insects due to varying levels of plant defense and corresponding insect adaptation. In this study four experiments were carried out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The development of the velvetbean caterpillar, Anticarsia gemmatalis Hübner (Lepidoptera: Erebidae) and the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), was negatively affected when larvae fed on leaves of the resistant genotype, older leaves from the lower part of plants or leaves from reproductive-stage soybeans [ 32 ]. Distribution and concentrations of nutrients and flavonoids of leaf age and plant stage in soybeans may explain the varying levels of antibiosis to the velvetbean caterpillar and the fall armyworm [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of the velvetbean caterpillar, Anticarsia gemmatalis Hübner (Lepidoptera: Erebidae) and the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), was negatively affected when larvae fed on leaves of the resistant genotype, older leaves from the lower part of plants or leaves from reproductive-stage soybeans [ 32 ]. Distribution and concentrations of nutrients and flavonoids of leaf age and plant stage in soybeans may explain the varying levels of antibiosis to the velvetbean caterpillar and the fall armyworm [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these effects are also due to the possible partitioning of chemical defenses that may have individual compounds expressed more in early and mid-stages. It has been suggested that there are higher levels of rutin, a type of secondary metabolite, in the early stages of soybean plants, which has been shown to retard the development of FAW at every stage and decrease pupal viability [ 49 , 50 ]. Further investigation is needed, as differential effects are shown in the literature, such as Souza et al [ 50 ] specifically finding that older leaves were more detrimental to FAW and another Lepidopteran pest, velvetbean caterpillar – Anticarsia gemmatalis .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there are higher levels of rutin, a type of secondary metabolite, in the early stages of soybean plants, which has been shown to retard the development of FAW at every stage and decrease pupal viability [ 49 , 50 ]. Further investigation is needed, as differential effects are shown in the literature, such as Souza et al [ 50 ] specifically finding that older leaves were more detrimental to FAW and another Lepidopteran pest, velvetbean caterpillar – Anticarsia gemmatalis . Studies by Mai et al [ 51 ] support our findings that earlier-stage soybeans were also detrimental to FAW.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor that we must point out is the possibility of the presence of phenolic substances in the leaves of soybean plants, which act as defense against herbivores that cause leaf injury [27], thus giving rise to another alternative, which in turn may explain the unusual behavior of this arthropod.…”
Section: Discussionmentioning
confidence: 99%